Triple-Reassortant Swine Influenza A (H1) in Humans in the United States, 2005–2009 - Shinde, Vivek; Bridges, Carolyn B; Uyeki, Timothy M; Shu, Bo; Balish, Amanda; Xu, Xiyan; Lindstrom, Stephen; Gubareva, Larisa V; Deyde, Varough; Garten, Rebecca J; Harris, Meghan; Gerber, Susan; et al. (The New England journal of medicine, 2009)
Influenza is known to infect several different hosts, including humans, birds, and pigs. The influenza genome is structured in a way that allows for rapid recombination between strains across host species. In this report, 11 sporadic episodes of human infection from novel swine-associated influenza viruses are documented and the associated clinical illness and virologic characteristics are described. In this report, 11 sporadic episodes of human infection from novel swine-associated influenza viruses are documented and the associated clinical illness and virologic characteristics are described. Pigs have been hypothesized to act as a mixing vessel for the reassortment of avian, swine, and human influenza viruses and might play an important role in the emergence of novel influenza viruses capable of causing a human pandemic. 1 – 3 Recent reports of widespread transmission of swine-origin influenza A (H1N1) viruses in humans in Mexico, the United States, and elsewhere highlight this ever-present threat to global public health. 4 , 5 Between the 1930s and the 1990s, the most commonly circulating swine influenza virus among pigs — classic swine influenza A (H1N1) — underwent little change. However, by the late 1990s, multiple . . .